L'Incubation est-il un nouveau roman? - Leduc-Park, Renée M. (My University, 1973)
In this thesis we propose to refute the idea frequently upheld by critics that L'Incubation is a “nouveâù roman”. We have attempted to point out the existence of an essentially psychoanalytic content in this novel to emphasize its classical aspects which are specifically rejected by Robbe-Grillet.
Keywords: French and Francophone Language and Literature; French and Francophone Language and Literature